Electrochemical degradation of petroleum hydrocarbons (PAHS) from synthetic aqueous solutions - Yaqub, A. (Maik Nauka-Interperiodica Publishing, 2017)
Water separated from crude oil and wastewater discharge from petroleum oil refineries contains significant quantity of dissolved hydrocarbons. Polycyclic aromatic hydrocarbons (PAHs) are major toxicants in wastewater of refineries. It is difficult to treat wastewater containing PAHs due to their recalcitrant property and low solubility. Conventional techniques for the treatment of wastewater are still a concern of toxicity. Electrochemical oxidation process has been found to be a favorable for treating wastewater. Electrodes with high stability and electrocatalytic activity are important factors for a successful electrochemical oxidation of toxic organics in wastewater. In this study titanium anodes were coated with tin, antimony and iridium oxide mixture from their respective salts by thermal decomposition method. FESEM and XRD used for surface characterization of Ti/SnO2–Sb2O5–IrO2 anode. Quantification of PAHs was done using GC–MS. Results confirm the presence of respective oxides on anode surface. Their electrocatalytic capability was tested for degradation of 16 priority PAHs in aqueous solution. Results reveal the complete degradation of naphthalene, acenaphthylene, acenaphthene and fluorene without using NaCl electrolyte. While in the presence of NaCl naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene and pyrene were completely removed. About 98 of total PAHs removal was found at all initial pH values 3, 6, and 9 in the presence of electrolyte. Current study will be helpful in improving quality of petroleum industry wastewater containing PAHs. © 2017, Pleiades Publishing, Ltd.